The Problem of Dualism in the Works of C. Ruiz Zafon - zvereva, Ekaterina; lutskovskaia, larisa (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study is to provide a general description of the author’s esthetic picture of the world and the analysis of the phenomenon of duality. The author uses a set of complementary methods and methods of literary analysis, the basic of which are biographical and structural methods. Particular attention is paid to the category of duality and its manifestation in the ethical dualism of Good and Evil, their identical duality. The article deals with the problem of existential duality − the immanent property of the author’s conceptual, mythopoetic and linguistic pictures of the world. Within the artistic structure of duality Zafón develops social reality, matching it with the universal opposition “life / death”; the inclusion of external and internal duality always emphasizes the author’s aesthetic attitude to reject the contemporary reality. The materials of the article are of practical value for further understanding of the problem of duality as an archetype of culture and language, its comprehension as a philosophical and artistic category.